The Impact of the Business Cluster Program on Micro Business Growth Through a Green Economy Approach - Nofriady, Hery; Ellanto, Kenny; Pradwipa, Ayodya; Indriani, Farida; Muharam, Harjum (Research Horizon, 2024)
This study aims to measure the impact of the BRI Business Cluster Program on micro enterprises growth through a green economy approach at BRI Pasar Kodim Pekanbaru. This research used a quantitative method with data collection techniques through questionnaire surveys and secondary data analysis. The research population is the Business Cluster Program at BRI Pasar Kodim Pekanbaru, with a sample of 13 micro enterprises at Gerai Kembang Setaman. The results of the linear regression analysis show that micro enterprises growth (X) has a significant impact on environmental sustainability (Y) with the regression equation Y=18.058+0.405X. The ANOVA test results show an F value of 15.179 with a p-value of 0.002, indicating that the regression model is significant at a 95% confidence level. The R Square value of 0.580 indicates that 58% of the variability in environmental sustainability is explained by this model. Descriptive analysis shows significant improvements in various aspects of micro enterprises after joining the BRI Business Cluster Program, such as increases in monthly turnover, number of employees, and the use of QRIS/EDC. These findings reflect the program's success in promoting business growth and environmental sustainability through the application of the green economy.